2022
DOI: 10.1021/acssensors.1c02061
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin G Protein-Coupled Receptor-Based Biosensing Modalities in Yeast

Abstract: Serotonin is a key neurotransmitter involved in numerous physiological processes and serves as an important precursor for manufacturing bioactive indoleamines and alkaloids used in the treatment of human pathologies. In humans, serotonin sensing and signaling can occur by 12 G protein-coupled receptors (GPCRs) coupled to Gα proteins. In yeast, human serotonin GPCRs coupled to Gα proteins have previously been shown to function as whole-cell biosensors of serotonin. However, systematic characterization of seroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
(185 reference statements)
0
5
0
Order By: Relevance
“…In addition, despite the fact that human GPCRs typically work in yeast at neutral pH [23][24][25] , CB2R showed prohibitively strong constitutive signaling at pH 7.1 (a phenomenon also previously noted with the heterologously expressed serotonin receptor 26 ). When the biosensor was assayed at pH 5.8, we observed greatly reduced background with both AEA and 2-AG.…”
Section: Engineering Cannabinoid Receptor Function In Yeastmentioning
confidence: 57%
“…In addition, despite the fact that human GPCRs typically work in yeast at neutral pH [23][24][25] , CB2R showed prohibitively strong constitutive signaling at pH 7.1 (a phenomenon also previously noted with the heterologously expressed serotonin receptor 26 ). When the biosensor was assayed at pH 5.8, we observed greatly reduced background with both AEA and 2-AG.…”
Section: Engineering Cannabinoid Receptor Function In Yeastmentioning
confidence: 57%
“…Naturally, GPCRs allow for concentration- dependent signal transduction to provide outputs of regulated intensity, and display exceptional diversity to sense various types of ligands, ranging from light rays and small molecules to peptides and larger complex proteins 53,56,68,69 . Genes encoding GPCRs MTNR1A 53 , ADORA2B 53 , ADRA2A 54 , 5HT4b 70 , Mam2 53 , and CXCR4a 71 were chosen accordingly, and individually heterologously expressed and coupled to either native Gpa1 or the chimeric G ɑZ or G ɑi1/2 -subunits in the optimized background strain employing display of CD19 from P FUS1 (strains DIX57-58). The constructed GPCR library covered sensing of small molecules (melatonin, adenosine, adrenaline, serotonin), peptides (P-factor), and complex proteins (CXCL12/SDF-1)( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Primers, DNA fragments, amplicons, plasmids, and gDNA were always dissolved in Milli-Q H2O and stored at -20°C. An overview of parts, backbones, constructed plasmids, and plasmids originating from other studies [52][53][54]57,58,67,70,71,84,86 can be found in Suppl. Table 11-12, and primers in Suppl.…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
“…The genetic devices reported here might hold great promise for future metabolic engineering and biosensor applications. 52 , 53 , 54 Given that GPCRs are widely distributed in nature, 55 , 56 the plasticity of our genetic circuits would offer a variety of user-defined expression profiles, which are of significant interest to the synthetic biology and metabolic engineering community.…”
Section: Discussionmentioning
confidence: 99%